Prediction of the skin sensitization potential of polyhexamethylene guanidine phosphate, oligo(2-(2-ethoxy)ethoxyethyl) guanidinium chloride, triclosan, and mixtures of these compounds with the excipient propylene glycol through the local lymph node assay: BrdU-FCM. (October 2019) - Joo, Su-Jeong; Gautam, Ravi; Lee, JaeHee; Kim, HyeonJi; Yang, SuJeong; Jo, JiHun; Acharya, Manju; Maharjan, Anju; Kim, YeonGyeong; Lim, Yeon-Mi; Kim, ChangYul; Kim, HyoungAh; et al.
The guanidine family of antimicrobial agents, which includes polyhexamethylene guanidine phosphate (PHMG) and oligo(2-(2-ethoxy)ethoxyethyl) guanidinium chloride (PGH), and chlorophenol biocidal chemicals such as 2, 4, 4′-trichloro-2′-hydroxydiphenyl ether (triclosan) are used in various occupational and environmental biocidal applications. The excipient propylene glycol (PG) is used to dissolve the active ingredients. The skin sensitization (SS) potential of these substances has not been systemically investigated and is still debated. Moreover, mixtures of PHMG, PGH, or triclosan with PG have not been evaluated for SS potency. An in vivo assay known as the local lymph node assay: 5-bromo-2-deoxyuridine-flow cytometry method (LLNA: BrdU-FCM) was recently adopted as an alternative testing method and was used to address these issues. Via the LLNA: BrdU-FCM, PHMG, PGH, and triclosan were predicted to be sensitizers, while PG was predicted to be a nonsensitizer. In addition, d -limonene, which is used as a flavoring in various consumer products, was also predicted to be a sensitizer, although no unanimous conclusion has been reached regarding its SS potential. Mixtures of PHMG, PGH, triclosan, or d -limonene with PG at ratios of 9:1, 4:1, and 1:4 (w/w) were all positive in terms of SS potential, indicating that the PG excipient does not influence the SS predictions of these chemicals. Since humans can be occupationally and environmentally exposed to mixtures of excipients with active ingredients, the present study may give insight into further investigations of the SS potentials of various chemical mixtures.